Decomposing Integrated Assessment Climate Change - Christoph Böhringer; Andreas Löschel; Thomas F. Rutherford (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
We present a decomposition approach for integrated assessment modeling of climate policy based on a linear approximation of the climate system. Our objective is to demonstrate the usefulness of decomposition for integrated assessment models posed in a complementarity format. First, the complementarity formulation cum decomposition permits a precise representation of post-terminal damages thereby substantially reducing the model horizon required to produce an accurate approximation of the infinite-horizon equilibrium. Second, and central to the economic assessment of climate policies, the complementarity approach provides a means of incorporating second-best effects that are not easily represented in an optimization model.
Keywords: D61; D58; C63; C61; 330; integrated assessment; decomposition; terminal constraints; optimal taxation; Klimaschutz; Optimale Besteuerung; Wirtschaftspolitische Wirkungsanalyse; Wohlfahrtseffekt; Dekompositionsverfahren; Theorie